FIGURATIVE LANGUAGE IN JOHN MAYER’S SELECTED SONGS: A STYLISTIC ANALYSIS - Syahputra, Fikry (TALENTA, 2022)
This research identified and described the figurative language found in five selected John Mayer songs with broken heart themes. The method used in this study is a qualitative descriptive method. Based on the analysis, hyperbole dominates in this study. Songwriters use hyperbole in the song lyrics to emphasize to the listeners what the songwriter wanted to say or what he'd done in his life, the writer used hyperbole to represent his feelings and to express what he wants to say. John Mayer''s selected songs contain meanings beyond the sentence or figurative language. 31 sentences use figurative language in the song lyric, hyperbole is the most dominant type of figurative language that appears in this song because it is used to emphasize a situation or condition for special effects. The use of hyperbole is what then makes the pieces very beautiful and meaningful as it is known that hyperbole is used to strengthen the impression by exaggerating, this is what then gives a strong impression on some of the song lyrics.